Debt and development crises in Latin America : the end of an illusion - Griffith-Jones, Stephany; Sunkel, Osvaldo (Oxford [Oxfordshire] : Clarendon Press ; New York : Oxford University Press, 1986)
The book highlights the severity of the crisis in economic growth and development in Latin America, the increasing contradictions of the Latin American development model, many of which were both postponed and accentuated by the vast expansion of private international lending and borrowing that occurred in the seventies.
Includes bibliographical references and.index
usc 21/05/2018
Loans
Keywords: Debts, External; International finance; Economic history; Latin America